(untitled) (Journal of Engineering, 2014)
Architecture forms theoretical summaries and multi systems that have the essence of change, and that what distinguishes Architecture from other sciences and their systems. Architecture means way of life via its expressional products and that appears through its systems. These systems are based on formative and technological properties in form, structure, services and materials as well as their moral forms. All these are associated with techniques and facilities in order to establish integrated system. Architectural creation does not come from void but it depends on a conception base to create a new condition for creative architectural product. The general problem of the research concentrated on limited theoretical and practical studies, related to the effect of the technological systems integration on the expressional sides of architectural form in general. Besides, the absence of clear concept about the expressional aim in treatment type of technological systems of architectural form. Therefore, the research, in general, aimed to diagnose the effect of technology as a main factor to reveal the formal expression and creation, and to define items of architectural expression, and correlation with its implementation by mechanical treatment for architectural form. So, the research assumes the presence of direct expressional effects in structural and mechanical systems on the architectural form. Each of these systems has two functions: the first one is supplying the practical role, while the second function concentrated on the implementation of the expressional possibilities of architectural product form